2015
DOI: 10.1111/tbj.12430
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis, a Radiographic, Clinical, and Histopathologic Review

Abstract: Mastitis is a benign inflammatory process of the breast with heterogeneous histopathological findings, which clinically and radiographically may mimic a mammary carcinoma. We undertook a retrospective study on 37 cases of mastitis in our institution to correlate the radiographic imaging features and the clinical presentation with the histopathological findings. Histologically, there were 21 granulomatous, 7 fibrous, 3 plasma cell, 3 lupus, 2 lymphocytic, and 1 case of acute mastitis. Radiographically, 16/25 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
0
30
0
2
Order By: Relevance
“…(17). However, it should not be forgotten that the radiological findings of granulomatous lobular mastitis are not characteristic and do not provide benefit in distinguishing between benign and malignant disease (18)(19)(20)(21). Ultrasonography results in our study showed an irregularly limited hypoechoic area and a concentrated fluid collection.…”
Section: Discussionmentioning
confidence: 50%
“…(17). However, it should not be forgotten that the radiological findings of granulomatous lobular mastitis are not characteristic and do not provide benefit in distinguishing between benign and malignant disease (18)(19)(20)(21). Ultrasonography results in our study showed an irregularly limited hypoechoic area and a concentrated fluid collection.…”
Section: Discussionmentioning
confidence: 50%
“…Historically, many histologically proven cases of granulomatous lobular mastitis have been termed “idiopathic,” as specific etiologies for inflammatory host responses in such patients were undetermined . Treatments for idiopathic disease states are empiric, often leading to management dilemmas and uncertain outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mastopathies are most commonly encountered in breastfeeding women who report clinical symptoms of pain, erythema and swelling. Such conditions are often treated with antimicrobial agents and may require surgical intervention in settings complicated by abscess formations . Such inflammatory disorders of the breast may be associated with significant morbidity and in some instances may lead to disfigurement.…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows that the frequency of IGM in Egypt approximates those in Turkey and Iran [21,28]. On the contrary, Western countries like the USA [15], the UK [5], and New Zeeland [20] have a remarkably lower rate of IGM. Our work, as well as that of others [20,28,29], revealed that IGM is usually seen in women who are lactating or those who have been lactating.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is rich with histologic studies of IGM. However, these studies have included a relatively small number of cases ranging from case reports to a maximum of 29 cases [11,12,13,14,15,16]. Fine-needle aspiration cytology (FNAC) in IGM has also been investigated in several reports with controversial results [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%